Development a Local Wisdom-Based Ratio E-Worksheet Based on Critical Thinking Indicators - Rahaju Rahaju; Tatik Retno Murniasih; Sri Hariyani; Sumaji Sumaji (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2026)
Critical thinking skills are essential for dealing with various problems in life problems. However, many students still demonstrate low levels of these skills. This study aimed to develop a local wisdom-based ratio electronic student worksheet (E-Worksheet) designed based on critical thinking indicators and to examine its validity and practicality. The study adopted the Plomp development model, consisting of preliminary research, prototyping, and assessment phases. The participants were seventh-grade students in Singosari District, involving a small group of 10 students and a large group of 24 students. The developed web-based E-Worksheet integrates local wisdom contexts, such as Singhasari cultural heritage, Kirab Tirta Amarta Sari, and Petirtaan Watugede, into ratio learning. The validation results showed an average score of 94. 44%, categorized as highly valid. The practicality results indicated scores of 89. 29% from teachers and 80. 12% from students, both categorized as highly practical. These findings indicate that the developed E-Worksheet is valid and practical for use in mathematics learning and systematically designed based on critical thinking indicators. It has the potential to support meaningful and contextual learning. Further research is recommended to examine its effectiveness in improving students’ critical thinking skills.